PENDIDIKAN MULTIKULTURAL DALAM PERSPEKTIF ADAT MINANGKABAU - Ismael, Fauzan; Aprison, Wedra (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
Writing this article aims to examine the phenomenon of diversity which has become the nature of the Indonesian nation including the Minangkabau in dealing with the changing times which have given birth to new cultures and habits in the midst of a society whose basis is already diverse. The writing method used in this study is a literature study with data sources obtained through books, scientific papers,articles, websites which are collected and analyzed. The results of the research show that Minangkabau custom is a custom that is based on values ​​originating. That value is contained in the customs carried out by the community so that they become human beings with a dignified value and ethics. If we talk about changing times, there will be no Minangkabau custom that can change it. Minangkabau custom also teaches about